Implikasi Klinis Gambaran Elektrokardiogram Low-voltage - Andrianto Andrianto; Putri Rachmawati Dewi (Jurnal Kardiologi Indonesia, 2016)
Low-voltage on the surface electrocardiogram (ECG) is classically defined as peak-to-peak QRS voltage less than 5 mm in all limb leads and less than 10 mm in all precordial leads. There are many causes of low QRS voltage (LQRSV), and they can be differentiated into those due to the deficient heart’s generated potentials (cardiac causes) and those due to the attenuating influences of the pericardial space and pericardium, or the passive body volume conductor, enveloping the heart (extracardiac causes). In some patients, LQRSV voltage may only represent a normal variant. The ECG challenge for this issue is to examine the physiological, anatomical and electrical equipment problems of low-voltage, or low-amplitude, ECG and to suggest methods for troubleshooting the low-voltage ECG to ensure reliable cardiac monitoring.